Reference Power Tracking for AC Charging of Electric Vehicles - Federico Ferretti; Antonio de Paola; Harald Scholz; Stefano Tarantola; Evangelos Kotsakis (IEEE Access)
Electric vehicle (EV) charging is widely considered as a key enabling technology that can support system stability and provide ancillary services to the grid. The present work aims to advance the state of the art in dynamic charging of individual EVs within existing AC-charging facilities. The paper proposes two alternative control solutions for tracking of power setpoints in EVs, based on adaptive feedforward and feedback linear controllers, respectively. The control design, which does not require any ad-hoc hardware adjustment of the standard EV charging infrastructure, nor higher-level communication, is supported by extensive real-world tests that have been performed on the workplace charging facility operated in the JRC Ispra campus. The experimental results validate the effectiveness of the proposed control methods in tracking two different current profiles for flexibility scheme qualification.